Business awareness in the management of a modern organisation regarding the usage of selected information technologies - Filip Rembisz; Piotr Zaskórski (Nowoczesne Systemy Zarządzania)
Research objectives and hypothesis/research questions The aim of the paper is to identify selected information technologies as a component of strengthening the potential of modern organizations to ensure information efficiency and shape the appropriate level of situational awareness of decision-makers and employees. The entire study is profiled by the hypothesis that: modern information technologies improve the processes of management and creating the necessary level of situational awareness of various entities in the aspect of ensuring the effectiveness of business processes.